Descrição dos episódios de candidemia de origem nosocomial no Hospital Universitário Cassiano Antônio de Moraes - Rueda, Jacqueline Oliveira (2006)
This work was a descriptive study, which described the episodes of nosocomial candidemias occurring at Hospital Universitário Cassiano Antônio de Moraes (HUCAM), between March 1st, 2003 and February 28th, 2006. Its aim was to define the rates of prevalence and mortality of these epidsodes, to identify the species involved and to relate the frequency of the risk factors among adults and newborn (NBs), as well as the epidsodes among candidemias caused by Candida albicans (CA) and Candida non-albicans (CNA). The methodology included the cases in a consecutive way, as positive hemoculture was detected for these fungi. The date collection of patients was based on the medical records, through a standard form and it was analyzed using the Social Package Statistical Science program, including 45 cases of candidemias, being nineteen cases (42%) in NBs. It was observed that the incidence of nosocomial candidemia at HUCAM was 2.0/10.000 patient-day, 1.9/1.000 discharges and 16/10.000 admissions, being greater in patients interned in intensive therapy unity. the CNA predominated and C. parapsilosis was more incidente among the NBs; the group of susceptible more involved were those interned for 3 weeks with acute septical syndrome and in use of antibiotics; the frequency of risk factor was similar among the episodes due to CA and the ones due to CAN; greater utilization of total parenteral nutrition was found in the NBs and the dialysis, among the adults (p< 0,005); the total mortality rate was 44% among adults and 58% among the NBs. And the attributed mortality rate was 16 in adults and 26% in NBs. It was concluded that incidence of candidemias at HUCAM was high and associated with substantial mortality.